2015
DOI: 10.1371/journal.pone.0129623
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry Based Detection and Isolation of Plasmodium falciparum Liver Stages In Vitro

Abstract: Malaria, the disease caused by Plasmodium parasites, remains a major global health burden. The liver stage of Plasmodium falciparum infection is a leading target for immunological and pharmacological interventions. Therefore, novel approaches providing specific detection and isolation of live P. falciparum exoerythrocytic forms (EEFs) are warranted. Utilizing a recently generated parasite strain expressing green fluorescent protein (GFP) we established a method which, allows for detection and isolation of deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…The traversal activity of sporozoites was measured using the standard cell-wounding assay described in (Dumoulin et al, 2015). Briefly, 5 × 10 4 HC-04 cells were seeded into each well of a 48-well plate (Corning, Sigma-Aldrich) that had been coated with type IV rat-tail collagen.…”
Section: Cell Traversal Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The traversal activity of sporozoites was measured using the standard cell-wounding assay described in (Dumoulin et al, 2015). Briefly, 5 × 10 4 HC-04 cells were seeded into each well of a 48-well plate (Corning, Sigma-Aldrich) that had been coated with type IV rat-tail collagen.…”
Section: Cell Traversal Assaymentioning
confidence: 99%
“…Although P. falciparum sporozoites traverse human macrophages and hepatocytes in vitro (Behet et al, 2014;Dumoulin et al, 2015;van Schaijk et al, 2008;, there is a paucity of knowledge surrounding the molecular basis for these events (reviewed by Yang & Boddey, 2017). Recently, it was shown that GAPDH on the sporozoite surface interacts with CD68 on Kupffer cells to facilitate traversal through the macrophages (Cha, Kim, Pandey, & Jacobs-Lorena, 2016) and that SPECT and PLP1 are essential for P. falciparum traversal of hepatocytes .…”
Section: Introductionmentioning
confidence: 99%
“…falciparum in cryopreserved primary human hepatocytes has recently been reported [51] [52] Based on or results, and other published reports, we infer that primary human hepatocytes may be a better system than the HCO-4 cell line to study the development and growth of liver form P . falciparum parasites [53]. …”
Section: Discussionmentioning
confidence: 99%
“…Primary mouse hepatocytes and mouse cell lines, have had infectivity's lower than 6 and 2%, respectively, using RMPs, based on immunofluorescence microscopy or flow cytometry ( Table 3). The lower infectivity's observed are a typical feature of malaria liver-stage infection and depend not only on the origin of the host cells and strain of parasite, but also on the expression of CD81 receptor, which has been described as essential for primary human hepatocyte invasion (107,109). The infectivity may vary due to the expression levels of EhpA2 (110) and the class B, type I scavenger receptor (SR-BI) (111).…”
Section: Infectivitymentioning
confidence: 99%